Community integration outcomes of people with spinal cord injury and multiple matched controls: A pilot study. (27th December 2016) - Callaway, Libby; Enticott, Joanne; Farnworth, Louise; McDonald, Rachael; Migliorini, Christine; Willer, Barry
Abstract : Background/aim: Australia's National Disability Insurance Scheme (NDIS) is designed to influence home, social and economic participation for Scheme participants. Given the major disability reform underway, this pilot study aimed to: (i) examine community integration outcomes of people with spinal cord injury (SCI); (ii) compare findings with multiple matched controls and (iii) consider findings within the context of Australia's NDIS. Methods: Setting: Victoria, Australia. Design: Matched analysis (people with and without SCI). Instrumentation: Community Integration Questionnaire (CIQ). Participants: n  = 40 adults with SCI (M age = 52.8 years; 61% male; 77% traumatic SCI). Analyses: Matched analyses from each SCI subject aged <70 years ( n  = 31) with four CIQ normative data subjects (from n  = 1927) was undertaken, with key demographic variables matched (age range, gender, living location and living situation). Risk of low CIQ score as a function of SCI was also examined using conditional Poisson regression. Results: With key demographic variables held constant, small to medium effect sizes were found in favour of the normative sample, with statistically significant differences in home (ρ = 0.003) and productivity integration (ρ = 0.02). Relative risk of low home integration was significant in the SCI cohort (conditional RR (95% CI) = 3.1 (1.5–6.3), ρ = 0.001). Relative risk of low CIQ total, social integration and productivity scores did not reach significance. Conclusion: This cohort of SCI participants was less integrated into home and productive occupations than matched norms, holding implications for planning and allocation of supports to influence outcomes within an NDIS. Further research is necessary to understand community integration outcomes in larger matched samples.